Analysis of results determination of level of vascular endothelial growth factor, receptor for vascular endothelial growth factor and big endotelin-1 in structure of arteriovenous malformations - I.V. Altman (Українська Інтервенційна Нейрорадіологія та Хірургія, 2022)
Objective ‒ to assess the diagnostic significance of angiogenesis factors based on the study of the level of angiogenesis factors (vascular endothelial growth factor (VEGF-A), specific receptor for vascular endothelial growth factor (VEGFR-1), endothelial inflammation factor (Big Endothelin-1)) in arterial and venous blood of patients with arteriovenous malformations (AVM) and healthy individuals without AVM. Materials and methods. In 2019–2021 a study according to the data of enzyme-linked immunosorbent assay the level of VEGF-A, VEGFR-1 and Big Endothelin-1 in the plasma of arterial and venous blood of 50 (19 (38.0 %) men and 31 (62.0 % women)) with AVM of different localization was carried out. The age of patients ranged from 3 to 51 years, the mean age ‒ (27.79 ± 2.19) years. The control group consisted of 35 healthy individuals (20 men and 15 women) without AVM. Patients with AVMs were divided into two groups: with small and medium-sized AVM in the stage of compensation (n=32) and with large and giant AVM in the stage of subcompensation or decompensation (n=18). Results. A significant (p < 0.05) difference was proved between the concentration of VEGF-A, VEGFR-1, Big Endothelin-1 in the plasma of arterial and venous blood of patients with AVM. This fact proves that the processes of pathological angiogenesis occur precisely in the structure of AVM. The value of VEGF-A, VEGFR-1 and BE-1 in patients with small and medium AVM was higher than in healthy individuals. The VEGF-A level was significantly (p < 0.05) in 2.4 times higher than in the control group, the VEGFR-1 level ‒ in 1.4 times, and the ET-1 level ‒ in 1.5 times. The value of VEGF-A, VEGFR-1 and BE-1 level in patients with large and giant AVM was significantly (p < 0.05) higher than in healthy individuals: VEGF-A ‒ in 7.2 times, VEGFR-1 ‒ in 2.36 times, and BE-1 ‒ in 1.7 times. Conclusions. The data obtained make it possible to statistically reliably state that the processes of pathological angiogenesis occur directly in the structure of AVM. A statistically significant dependence of the level of VEGF-A, VEGFR-1 and BE-1 in the blood plasma of patients on the size of the AVM and the stage of its compensation was revealed.